Wideband printed monopole antenna for application in wireless communication systems. Issue 7 (4th April 2018) - Alibakhshikenari, Mohammad; Virdee, Bal S.; See, Chan Hwang; Abd‐Alhameed, Raed; Ali, Abdul; Falcone, Francisco; Limiti, Ernesto
Abstract : Empirical results of an electrically small printed monopole antenna are described with a fractional bandwidth of 185% (115 MHz to 2.90 GHz) for return‐loss better than 10 dB, peak gain and radiation efficiency at 1.45 GHz of 2.35 dBi and 78.8%, respectively. The antenna geometry can be approximated to a back‐to‐back triangular shaped patch structure that is excited through a common feed‐line with a meander‐line T‐shape divider. The truncated ground‐plane includes a central stub located underneath the feed‐line. The impedance bandwidth of the antenna is enhanced with the inclusion of meander‐line slots in the patch and four double split‐ring resonators on the underside of the radiating patches. The antenna radiates approximately omni‐directionally to provide coverage over a large part of very high frequency, the whole of ultrahigh frequency, the whole of L‐band and some parts of S‐band. The antenna has dimensions of 48.32 × 43.72 × 0.8 mm 3, which is corresponding to the electrical size of 0.235 λ 0  × 0.211 λ 0  × 0.003 λ 0, where λ 0 is the free‐space wavelength at 1.45 GHz. The proposed low‐profile low‐cost antenna is suitable for application in wideband wireless communications systems.